Determinants of retirement savings - Yusof, Radduan; Sabri, Mohamad Fazli (2017)
Global demographic changes and retirement savings adequacy have emphasised on voluntary pension as a new paradigm for the retirement system. This has led to many types of research pertaining to the development of the private retirement system. The effort was followed by making the mandatory Second Pillar and voluntary Third Pillar of the social security system as more financially sound and important. This is to encourage contributors to the retirement fund to switch focus from a less generous pension-guaranteed-defined benefit system to a more individualistic-defined contribution plan. This review article collected, compiled, and reviewed selected articles on the determinants of retirement savings and planning. It was sourced from several electronic databases in an attempt to group the determinants into different categories. The input from the reviews was then categorised into economics, socioeconomics, and non-economics sub-categorical behavioural, psychological, and demographic determinants and its application, as reported in researches pertaining to retirement savings and planning of the near decade. Some suggestions were made in light of the analysis.